Pemikiran Teodisi Said Nursi tentang Bencana Alam: Perpaduan Pemikiran al-Ghazali dan al-Rumi - Maftukhin Maftukhin (Universitas Darussalam Gontor, 2018)
This article explores Said Nursi’s concept of theodicy on natural disasters and human misery. The problem of natural disasters and human misery is one of the important themes in the Islamic debate where trust in the Almighty and Most Merciful God occupies a central position in the faith system. The theme is related to the concept of ‘God’s justice’. When Nursi raised the topic, it was known that Bediuzzaman Said Nursi was influenced by two great medieval Islamic thinkers, namely al-Ghazali and al-Rumi. These two thinkers had a major influence on Said Nursi’s thinking on the theodicy problem. Nursi explores natural disasters, misery and human suffering as a matter of theodicy. Nursi argued, it was through suffering that humanity underwent trials and tribulations. Natural disasters and misery that befall on humans are seen by Nursi as a test and trial for human beings. This article finds that Nursi was of the view that these trials and tests have a purpose as a means for developing the spiritual potential and to find a way toward God. Nursi’s point of view of the theodic problem of natural disasters and human misery has a close relationship with that of al-Ghazali and al-Rumi. If al-Ghazali emphasized the aspect of God’s omnipotence, al-Rumi built his teachings on the basis of love. But in Nursi’s hands these two thinkings can be properly combined.